2021
DOI: 10.1111/jssr.12765
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Resilience After Cancer via Religion/Spirituality: Spiritual Capital Through a Life Course Lens

Abstract: Religious beliefs and practices are thought to help people confront problems that push the limits of human life. Integrating the life course perspective, we assess whether the accumulation of religiosity ("spiritual capital") between childhood and adulthood had any bearing on its ability to cushion the mental health insults of a cancer diagnosis, factoring in age-at-diagnosis. Using two waves of data from National Survey of Midlife Development in the United States (N = 1431), results suggest that stable high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…Relatedly, couples in our study reported that, according to their beliefs, the occurrence of the illness is predestined, which facilitated their acceptance. It also appears that religious and spiritual beliefs may help to provide meaning to the cancer experience, develop positive attitudes toward suffering, and reduce the risk of depression [ 57 , 58 , 59 ]. Different studies conducted in Saudia Arabia, Iran, Turkey, Malaysia, and Tunisia report that the belief in “Qadr Allah” for Muslims facilitates acceptance of a cancer diagnosis by reminding them that their illness was part of God’s plan [ 60 , 61 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Relatedly, couples in our study reported that, according to their beliefs, the occurrence of the illness is predestined, which facilitated their acceptance. It also appears that religious and spiritual beliefs may help to provide meaning to the cancer experience, develop positive attitudes toward suffering, and reduce the risk of depression [ 57 , 58 , 59 ]. Different studies conducted in Saudia Arabia, Iran, Turkey, Malaysia, and Tunisia report that the belief in “Qadr Allah” for Muslims facilitates acceptance of a cancer diagnosis by reminding them that their illness was part of God’s plan [ 60 , 61 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthering this literature, religion studies have empirically explored the mechanisms through which religiosity and spirituality strengthen resilience after traumatic experiences such as disasters (Ai et al 2013), adverse conditions (Reutter and Bigatti 2014), challenging life events (Eliassen, Taylor, and Lloyd 2005), and health shocks (Upenieks 2022). The study of religious importance during adverse times has also focused on the challenges in the therapeutic use of religion We contribute to this large multidisciplinary literature by using data on religious importance from over 2 million Americans between 2008 and 2015 to determine whether the relationship between natural disasters and religious importance holds in the context of the United States, which has a substantial emergency management response system in comparison to many other countries (particularly low-and middle-income countries).…”
Section: Introductionmentioning
confidence: 99%
“…Furthering this literature, religion studies have empirically explored the mechanisms through which religiosity and spirituality strengthen resilience after traumatic experiences such as disasters (Ai et al. 2013), adverse conditions (Reutter and Bigatti 2014), challenging life events (Eliassen, Taylor, and Lloyd 2005), and health shocks (Upenieks 2022). The study of religious importance during adverse times has also focused on the challenges in the therapeutic use of religion (Kwilecki 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A focus on the evolution of religious capital necessarily implies understanding religiosity from a longitudinal perspective as a process of change and development (Hwang et al 2022b; Upenieks 2021). Religious activities and understandings practiced over a lifetime might serve to both increase one's confidence in the truth of their religion as well as strengthening emotional ties to religion and one's religious community.…”
Section: Introductionmentioning
confidence: 99%